Membentuk Karakter Peserta Didik melalui Pendidikan Agama Islam: Studi pada TK Daru Musthafa Al-Jannah - Agustina, Nelly; Saputra, Anri; Thahir, Jamilah; Harahap, Rizky Afriyanti; Hotimah, Fatimatu (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2023)
This study aims to explore the role of religious education in shaping the character of students at the Musthafa Aljannah Kindergarten, and to provide recommendations for improving learning approaches tailored to the needs of the students. The research method employed is qualitative with a descriptive approach, utilizing observation, interviews, and document analysis techniques. The results of the study indicate that religious education plays a significant role in shaping the values and character of students, with learning approaches suitable for children, such as role-playing, interactive storytelling, and artistic activities. The research recommendations include the need for active family involvement in religious education, the integration of religious values into the curriculum, and the development of creative learning methods appropriate for the students' developmental levels. It is hoped that the results of this research will contribute significantly to the understanding and implementation of religious education at the Musthafa Aljannah Kindergarten, serving as a basis for the development of more effective learning programs for shaping children's characters positively.